1978
DOI: 10.1159/000169914
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nitroglycerin Ointment in Congestive Heart Failure

Abstract: 7 consecutive patients with congestive heart failure refractory to standard therapy were treated with nitroglycerin ointment (GTNO). The pulmonary wedge pressure decreased from a control value of 30 ± 1 to 15 ± 1 mm Hg (mean ± SEM), and the arteriovenous oxygen difference narrowed from 6.8 ± 0.5 to 5.5 ± 0.3 ml%, after GTNO therapy. The heart rate decreased in 5 patients and the systolic blood pressure was either unchanged or decreased slightly. A reduction in the echocardiographic end diastolic dimension was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It was shown that both the hemodynamic and clinically beneficial effects of NTG ointment start within 30 min and last for at least 7 hours after application. The duration of action of NTG ointment in angina pectoris thus seems to be of the same order as in patients with congestive heart failure (2, 10,15). This also in agreement with recent pharmacokinetic studies on NTG ointment (2, 3, 16).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was shown that both the hemodynamic and clinically beneficial effects of NTG ointment start within 30 min and last for at least 7 hours after application. The duration of action of NTG ointment in angina pectoris thus seems to be of the same order as in patients with congestive heart failure (2, 10,15). This also in agreement with recent pharmacokinetic studies on NTG ointment (2, 3, 16).…”
Section: Discussionsupporting
confidence: 87%
“…In 10 patients with anginal pain at rest, the number of attacks was significantly reduced compared to placebo with a dosing interval of 6 hours (9). In congestive heart failure, the hemodynamic effects of NTG ointment last for &7 hours (2,(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Several studies have shown that nitroglycerin ointment has prolonged beneficial effects in the treatment of congestive cardiac failure (Chandraatna & Langerin, 1978;Hardarson et al, 1979;Franciosa et al, 1977). Armstrong et al (1980) has recently shown that application of GTN ointment significantly reduces pulmonary capillary wedge pressure for at least 240 min, and in some cases for up to 480 min.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the conventional administration routes and formulations, studies have been conducted to identify options with similar e cacy that can be easily administered. For human cardiac disease, these studies have led to the development of the sildena l citrate sublingual tablet to treat pulmonary arterial hypertension, nitroglycerin ointment to treat CHF, transdermal tulobuterol patch for bronchodilation, and transdermal beta-blocker (bisoprolol) patch to reduce postoperative atrial brillation (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%